Early Cambrian (Stage 4) brachiopods from the Shipai Formation in the Three Gorges area of South China. (May 2021) - Duan, Xiaolin; Betts, Marissa J.; Holmer, Lars E.; Chen, Yanlong; Liu, Fan; Liang, Yue; Zhang, Zhifei
Abstract: Diverse and abundant fossil taxa have been described in the lower Cambrian Shipai Formation in the Three Gorges area of Hubei Province, South China, but the taxonomy and diversity of the co-occurring brachiopod fauna are still far from clear. Here we describe the brachiopod fauna recovered from the Shipai Formation in the Three Gorges area of South China, including representatives of the subphylum Linguliformea: linguloids ( Lingulellotreta ergalievi, Eoobolus malongensis, and Neobolidae gen. indet. sp. indet.), and an acrotretoid ( Linnarssonia sapushanensis ); and representatives from the subphylum Rhynchonelliformea: the calcareous-shelled Kutorginates ( Kutorgina sinensis, Kutorgina sp., and Nisusia liantuoensis ). This brachiopod assemblage and the first occurrence of Linnarssonia sapushanensis shell beds permit correlation of the Shipai Formation in the Three Gorges area of Hubei Province with the Stage 4 Wulongqing Formation in the Wuding area of eastern Yunnan. This correlation is further strengthened by the first appearance datum (FAD) of the rhynchonelliform brachiopod Nisusia in the upper silty mudstone of both the Shipai and Wulongqing formations. The new well-preserved material, derived from siliciclastic rocks, also gives critical new insights into the fine shell structure of L . sapushanensis . Microstructural studies on micromorphic acrotretoids (like Linnarssonia ) have previously been restricted to fossils that were acid-etched from limestones. This is the first study to carry out detailed comparative ultrastructural studies on acrotretoid shells preserved in siliciclastic rocks. This work reveals a hollow tube and solid column microstructure in the acrotretoid shells from the Shipai Formation, which is likely to be equivalent of traditional column and central canal observed in shells dissolved from limestones.